How principals manage ethnocultural diversity: learnings from three countries - Billot, J; Goddard, JT; Cranston, N (Theopress Ltd for Commonwealth Council, 2007)
Global movements of people are resulting in increasingly diverse societies and principals are encountering more complex and challenging school communities. This paper presents the results of a tri-national study that sought to identify how principals manage ethnocultural diversity in schools in New Zealand, Australia and Canada. The research context of the three cities is provided by describing their ethnocultural diversity, relevant literature is examined and the research methodology discussed. Two major themes of the study findings are identified. Firstly, there appear to be similarities in the ethnocultural diversity evident in contemporary high schools in all three locations and how principals identified the effect of such diversity on their school. The second identifies similarities in how principals perceived and managed the resultant challenges in the three ethnoculturally diverse locations. Implications and conclusions from the findings are discussed, with suggestions for further research in this domain.